From single biobanks to international networks: developing e-governance. - Kaye, J (2011)
The future holds the possibility to link and network biobanks, existing biorepositories and reference databases for research purposes in ways that have not been possible before. There is the potential to develop 'research portals' that will enable researchers to access these research resources that are located around the globe with the click of a mouse. In this paper, I will argue that our current governance system for research is unable to provide all of the oversight and accountability mechanisms that are required for this new way of doing research that is based upon flows of data across international borders. For example, our current governance framework for research is nationally based, with a complex system of laws, policies and practice that can be unique to a jurisdiction. It is also evident that many of the nationally based governance bodies in this field do not have the legal powers or expertise to adjudicate on the complex issues, such as privacy and disclosure risks that are raised by cross-border data sharing. In addition, the conceptual underpinning of this research governance structure is based on the "one researcher, one project, one jurisdiction" model. In the conclusion of this paper, I lay out some preliminary ideas as to how this system has to change to accommodate research that is based on networks. I suggest that a move to digital governance mechanisms might be a start to making research governance systems more appropriate for the 21st century.